LAND SUITABILITY ANALYSIS OF WHITE SHRIMP (LITOPENAEUSVANNAMEI) AQUACULTURE IN THE COASTAL AREA OF BARRU DISTRICT SOUTH SULAWESI – INDONESIA - Andi Gusti Tantu; Suryawati Salam; Erni Indrawati; Andi Reski Puspita Ayu (Fish Scientiae, 2019)
The coastal area of Barru District has a wide brackishwater pond, but its productivity is relatively low. A research to determine land suitability as one of the brackish water pond productivity-raising projects is needed. Considerable factors in determining land suitability for white shrimp aquaculture covers topography and hydrology, soil conditions, water quality, and climate. Quality of water is observed during a rainy and dry season. Spatial analysis using Geographic Information System is applied in the determination of land suitability for shrimp aquaculture. The analysis shows the actual land suitability of the existing ponds in Barru district, namely 2.399 ha, where land is classified as highly suitable (S1 class), 232.94 ha (9.71%) classified as moderately suitable (S2 class), 1,444.20 ha (60.20%) classified as marginally suitable (S3 class), 721.14 (30.06%) and classified as marginally low suitable (N class), 0.72 ha (0.03%), Limiting factors during the rainy season are the flood, while salinity is the main limiting factor during a dry season. Generally, other limiting factors are of the water sources, low level of pH soil and roughness of soil texture in a certain area.